Promoting Research-Based School Reform: What Indonesian Teachers Expect - Sylvia, Novi; Hadiana, Deni (Proceedings International Conference on Education Innovation and Social Science, 2023)
Research culturization and structurization are essential for society in the current era of information acceleration. This significance is no exception and is highly specialized in educational institutions such as formal schools. Teachers as academic actors who are directly in contact with students know the ins and outs of the challenges faced at school. This study aims to analyze teachers' expectations of research-and-innovation-based school/madrasa (Sembari) as expectations shape perception and influence the implementation. A hundred teachers from Indonesia's primary, secondary, and senior education levels became the research object by completing the MIMPI Sembari questionnaire. The teachers support the implementation of culturization and structurization of research and innovation. Their expectations are holistic by including expectations for each structure, namely teachers, students, and the school, and the implementation of Sembari at school. The findings of this study shift the paradigm of research practice at schools, which are only concerned with a culture of research competition between students. These findings support the essential culturization and structurization of research at Indonesian schools and madrasas. Teachers' expectations represent the practical needs of teachers and teachers' observation of education practice at schools. Further research about school structure and culture can be developed by exploring schools' needs from various perspectives.